Apposite of atmospheric electric parameters with the energy coupling function (ε) during geomagnetic storms at high latitude - Kumar, C.P. Anil; Panneerselvam, C.; Nair, K.U.; Jeyakumar, H. Johnson; Selvaraj, C.; Gurubaran, S.; Venugopal, C. (2009)
In this paper we are concerned with the variation of the atmospheric electric field and the air–earth current due to the excessive power generated by the solar wind-magnetosphere dynamo during geomagnetic storms, recorded at Maitri in Antarctica during 2004. A major part of the power generated by the solar wind-magnetosphere dynamo is used in the formation of the ring current and the rest is utilized for Joule heating and auroral particle precipitation. The method adopted by Frank-Kamenetsky et al. [Frank-Kamenetsky A.V., Troshichev O.A., Burns G.B., Papitashvili V.O., 2001. Variations of atmospheric electric field in the near-pole region related to the interplanetary magnetic field. J. Geophys. Res. 106, A1, 179–190.] was utilized to delineate the variations due to the signatures of tropical thunderstorm activity from the geoelectric data; while statistical methods used in our earlier studies were used to delimit variation due to the constant buffeting of the solar wind. We find that the solar wind-magnetosphere energy coupling function (ε) to be well correlated with the atmospheric electric parameters during the onset of geomagnetic disturbances. However the correlation breaks down during minor storms and sub-storm events.